Sleep quality and duration following evening intake of alpha-lactalbumin: a pilot study - Ong, Jun N.; Hackett, Daniel A.; Chow, Chin-Moi (Biological rhythm research, 2017)
Tryptophan loading enhances sleep quality by increasing the ratio of plasma tryptophan to large neutral amino acids (TRP:LNAA) and consequently synthesis and availability of serotonin in the brain. Alpha-lactalbulmin (A-LAC) is rich in tryptophan and has the highest TRP:LNAA of all protein sources. This pilot study investigated the effect of an evening intake of A-LAC on objective and subjective sleep measures in male subjects without sleep complaints. Ten healthy male university students (aged: 26.9 ± 5.3 years; BMI: 21.7 ± 1.9 kg.m −2 ) participated in a double-blind, randomized, and placebo-controlled crossover counter-balanced study. Objective (actigraphy) and subjective (sleep log) sleep measures were recorded for two nights after a standardized evening meal supplemented with either A-LAC (20 g) or a placebo of sodium caseinate (20 g) one hour before bedtime. Evening A-LAC intake resulted in increased objective and subjective total sleep time by 12.8% (p = 0.037) and 10.8% (p = 0.013), respectively, compared to placebo. Objective sleep efficiency increased by 7.0% (p = 0.028) following A-LAC with no significant effects for other sleep indices. This pilot study demonstrates the efficacy of evening A-LAC intake on sleep quality in young healthy adults, however further large-scale studies are warranted to confirm the benefit.